Proliferative T cell responses to the human papillomavirus type 16 E7 protein in women with cervical dysplasia and cervical carcinoma and in healthy individuals - Luxton, Jenny C.; Rowe, Andrea J.; Cridland, Jeremy C.; Coletart, Timothy; Wilson, Philip; Shepherd, Philip S. (Journal of General Virology, 1996)
The levels of proliferative T cell responses to peptides representing the human papillomavirus type 16 (HPV-16) E7 protein have been measured using short-term T cell lines derived from peripheral blood of healthy women and those with cervical dysplasias and carcinoma of the cervix. In healthy individuals 47% (7/15) responded predominantly to the N- and C-terminal regions of the protein and 6/7 responders were to a single peptide between amino acids 80–94. In comparison 29% (9/31) of women with cervical dysplasia responded to HPV-16 E7, with a significantly reduced response to both the N- and C-terminal regions (P = 0.03 and 0.038, respectively). A higher proportion of responders was found in patients with high grade lesions (56%, 5/9) versus those with atypical or low grade histology (20%, 4/20) and the response to a single peptide between amino acids 75–94 was also increased in this patient group (P = 0.044). This may be a reflection of higher levels of current or previous exposure to HPV-16 in patients with high grade lesions. Correlation of T cell responses with HPV DNA type (detected by PCR of cervical biopsy tissue) showed that 3/9 (33%) HPV-16 DNA-positive individuals responded. This suggests that E7 may not be the dominant target of the immune response or that the response to E7 is down-regulated in these patients. In addition 4/18 (22%) HPV-16 DNA-negative individuals responded, suggesting that their T cells may have been primed by previous exposure to HPV-16 or that a cross-reactive response was detected. Proliferative T cell responses to both HPV-16 E7 and L1 were reduced in women with cervical carcinoma in comparison to those with cervical dysplasia and healthy controls. The observed down-regulation of responses to HPV-16 E7 in women with cervical dysplasia and cervical carcinoma may reflect an altered functional balance between subsets of T helper cells in HPV-16 infections.